1998
DOI: 10.1152/ajpheart.1998.275.5.h1726
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-induced ATP release from red blood cells requires CFTR activity

Abstract: Recently, it was reported that rabbit and human red blood cells (RBCs) release ATP in response to mechanical deformation. Here we investigate the hypothesis that the activity of the cystic fibrosis transmembrane conductance regulator (CFTR), a member of the ATP binding cassette, is required for deformation-induced ATP release from RBCs. Incubation of rabbit RBCs with either of two inhibitors of CFTR activity, glibenclamide (10 μM) or niflumic acid (20 μM), resulted in inhibition of deformation-induced ATP rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
361
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(381 citation statements)
references
References 21 publications
13
361
0
6
Order By: Relevance
“…Erythrocytes from various species, including human, release ATP and take up dye in a low-oxygen environment, when mechanically stressed, or when depolarized with a high concentration of potassium gluconate (6,32,50). Figure 6 shows that the osmotic stress-induced uptake of YoPro from the extracellular space by frog erythrocytes was inhibited by probenecid.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocytes from various species, including human, release ATP and take up dye in a low-oxygen environment, when mechanically stressed, or when depolarized with a high concentration of potassium gluconate (6,32,50). Figure 6 shows that the osmotic stress-induced uptake of YoPro from the extracellular space by frog erythrocytes was inhibited by probenecid.…”
Section: Resultsmentioning
confidence: 99%
“…However, this issue continues to be controversial. Glutamate-stimulated ATP release from microglia cells is significantly attenuated in cells isolated from CFTR knockout mice [82] and erythrocytes isolated from CF patients are reported to show no mechanical-induced ATP release [83]. Thus, a final verdict on this issue is premature.…”
Section: The Link To Cftrmentioning
confidence: 99%
“…This is potentially very important because it is known that some patient groups known to have low NO production or complications involving blood flow are also known to have RBCs that release lower than normal amounts of ATP upon pharmacological activation or physical deformation of the erythrocyte. Patients with primary pulmonary hypertension, 12 cystic fibrosis, 13 and diabetes 14,15 are example patient groups with these lower ATP release values. Figure 1 demonstrate that platelet NO can be measured via fluorescence spectrophotometry in tubing having a diameter that approximates an arteriole in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients with pulmonary hypertension 12 and cystic fibrosis 13 release less RBC-derived ATP upon mechanical deformation than the RBCs from healthy controls. Recently, in a separate study, it was reported that patients with type II diabetes mellitus released 91 ( 10 nM ATP versus 190 ( 10 nM ATP release in control RBCs.…”
Section: Discussionmentioning
confidence: 99%